FEATURES OF THE FORMATION OF LANDSCAPE-FALL FAILINGS IN HIGH-ALTITUDE CONDITIONS AT INDIVIDUAL MINING SITES (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: The article discusses the relevance of the problem, some issues of the mechanism of the development of landslide-failure caving (on the example of individual ore objects of the deposits of Uzbekistan). The research method included the study of not only the location of sinkholes, but also the sections located near sinkholes, since an important role in their formation is played by the flow of groundwater with active springs. In this regard, geophysical studies were carried out using the VES method, along the profile of the Guzhumsay field, which passes next to the sinkholes. As a result of the research, conclusions are drawn about the mechanism of development and the factors of the formation of failures and their influence on the development of deposits.